2006
DOI: 10.1002/gcc.20345
|View full text |Cite
|
Sign up to set email alerts
|

IGH switch breakpoints in Burkitt lymphoma: Exclusive involvement of noncanonical class switch recombination

Abstract: Most chromosomal t(8;14) translocations in sporadic Burkitt lymphomas (BL) are mediated by immunoglobulin class switch recombination (CSR), yet all tumors express IgM, suggesting an incomplete or exclusively monoallelic CSR event. We studied the exact configuration of both the nontranslocated IGH allele and the MYC/IGH breakpoint by applying a combination of lowand high-resolution methods (interphase FISH, DNA fiber FISH, long-distance PCR, and Southern blotting) on 16 BL. IGH class switch events involving the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Nevertheless, all these methods can fail to detect IG-M yc fusions [65]. The most reliable method is cytogenetic analysis by fluorescence in situ hybridization (FISH).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, all these methods can fail to detect IG-M yc fusions [65]. The most reliable method is cytogenetic analysis by fluorescence in situ hybridization (FISH).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly however, Myc, is typically expressed only when positively selected centrocytes are moving back to the DZ, where it is again suppressed [64,65]. Myc translocation patterns in sporadic BL suggest derivation from CSR events [66,67]. Therefore, one possibility is that low levels of AID activity [59,60,68] [34].…”
Section: Physiological Role Of E and Id Proteins In B Cell Developmentmentioning
confidence: 99%
“…In the endemic cases, EBV-positive MYC/Ig breakpoints originate from aberrant somatic hypermutation, while in the EBV-negative sporadic cases, MYC translocations mostly involve the Ig switch regions of the IGH locus. 191,192 In EBV-positive tumor cells, the growth-transforming program of viral gene expression (latency III) is extinguished, and only the EBV nuclear antigen (EBNA)1 is expressed via the alternative latency I program. Gene expression profiling studies in EBV-positive and -negative BL found significant differences in the expression of viral micro-RNAs and in selected target genes: LIN28B, CGNL1, GCET2, MRAS, PLCD4, SEL1L, SXX1, STK10/STK33L.…”
Section: Diffuse Large B-cell Lymphomamentioning
confidence: 99%